Investigation of the genetic aetiology of aminoglycoside-induced hearing loss in South African populations - Human, Hannique (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.